OsXTH19 Overexpression Improves Aluminum Tolerance via Xyloglucan Reduction in Rice Root Cell Wall - Akane Tatsumi; Teruki Nagayama; Ayumi Teramoto; Atsuko Nakamura; Ryusuke Yokoyama; Jun Furukawa; Hiroaki Iwai (Plants)
Aluminum (Al) dissolves from soil at low pH and is absorbed by plants, inhibiting their growth. Since most of the Al absorbed by plants is present in the cell wall, it is thought that the binding of Al to cell wall polysaccharides alters the properties of the cell wall and inhibits cell elongation. However, it remains unclear in which component of the cell wall Al accumulates. In this study, we determined the distribution of Al in rice root cell wall fractions under Al stress conditions. The results show that Al accumulates predominantly in the hemicellulose fraction, with star1 mutants accumulating significantly more Al than WT plants. An analysis of cell wall sugars revealed an increase in xyloglucan content under Al stress, which influenced the inhibition of root elongation. OsXTH19, a member of the xyloglucan endotransglucosylase/hydrolase (XTH) family, exhibits only xyloglucan endohydrolase (XEH) activity and lacks endotransglucosylase (XET) activity. OsXTH19 overexpressor rice (OsXTH19-OX) enhances the degradation of xyloglucan. Furthermore, OsXTH19-OX rice with reduced xyloglucan levels exhibited reduced Al accumulation and enhanced root growth under Al stress.